Pain management in acute otitis media: a qualitative study exploring GPs' views and expectations parallel to a trial of an educational intervention. Issue 4 (2018) - Uum, Rick T van; Sjoukes, Alies; Venekamp, Roderick P; Schilder, Anne GM; Groot, Esther de; Damoiseaux, Roger AMJ; Anthierens, Sibyl
No abstract available